ANALYSIS OF RESULTS OF COMPARATIVE INDUSTRIAL RESEARCHES OF OVER-THE-WHEEL DRILL AMORTIZERS OF DIFFERENT STRUCTURES - Мойсишин, Василь Михайлович; Лисканич, Михайло Васильович; Жовнірук, Роман Андрійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
According to the results of comparative industrial studies of over-the-wheel drill amortizes of various structures it has been established that the main power of the process of changing the vibration acceleration of the drilling column is in the field of low-frequency oscillations. The impact of different structures of shock absorbers on this power depends on the absorption coefficient of the elastic element of the shock absorber. It is established that the effectiveness of vibration protection (reduction of the amplitude of vibration acceleration of a drilling column) increases with increasing this coefficient.